Innovative Learning in the Age of Industry Revolution 4.0 - Shirley Gilbert; Allan Leslie White (Southeast Asian Mathematics Education Journal, 2018)
In 2018 the Indonesian Ministry of Industry (KPRI) released a document ‘Making Indonesia 4.0’, in response to the Fourth Industrial Revolution (4IR), setting out the Indonesian aspirations, the five focus sectors, the ten national priorities, the economic benefits, the job creation, and the next steps to ensure Indonesia’s future development. While all the ten priorities are important, of specific interest to education are: priority 5 that aims to advance network and digital platforms; e.g. 4G to 5G, Fiber speed 1Gbps, Data center and Cloud, and; priority 7, which aims to redesign the education curriculum and create a professional talent mobility program using a STEAM approach. A transformation of the schooling system is needed which is different to a reform as reform concentrates upon the existing structure and system whereas a transformation works to create different systems and structures. The basis for success lies in the hands of Indonesian teachers and lecturers. This paper will also discuss developments in brain research, and the teaching behaviours that are conducive to producing students with higher order and creative thinking skills and the ability to solve complex problems.